KARAKTER MORFOLOGI, SIKLUS HIDUP DAN PERILAKU PARASITOID, Trichogramma spp. ASAL DOLAGO KABUPATEN PARIGI-MOUTONG - Yunus, Mohammad (FAPETKAN UNTAD, 2005)
The aim of the research was to know about the morphology characters, live cycle, and behavioral of parasitoid Trichogramma spp. from Dolago. The research was conducted in May 2003 until October 2004. Spesimen got from field and observation was conducted in the laboratory. The result indicated that the spesimen from Dolago Parigi-Moutong was Trichogramma japonicum Ashmead spesies. The morphology characters were: male dan female was yellowish chocolate, red eyes and black thorax. Length body of adult was 0,4 - 0,5 mm and widely head 0,17 – 0,21 mm. Antenna type of female was capitate and male was filiform. The fore wings have trichia Rs1 as much 7-10 and in the boundary of wings growed some hairs. Long live of pra-adult phase was 8,2 + 0,3 days, the adult phase was 1,8 + 0,7 days and the total was 10,0 + 0.8 days. The adult parasitoid emerged from host-egg by infiltrating khorion. Immediately after it out of the host-egg, the adult look for the couple and copulation as soon as he can. Pra-Oviposition activities by female to get the compatible new host-egg. The Oviposition activities on the first day reach 15-30 times per female. On the second day, the oviposition activities remained 1-5 times or did not oviposition at all, than the adult immediately died. Key words : Trichogramma, japonicum, parasitoid, Scirpophaga innotata, paddy.